The role of strategic foresight in overcoming environmental sustainability challenges: A social framework based on discourse analysis for the Kingdom of Saudi Arabia - Alqahtani, Salman Fahad; Wani, Neelofar Hussain (Research Journal in Advanced Humanities, 2026)
Environmental sustainability in the Kingdom of Saudi Arabia is often discussed through the language of policy, investment, regulation, and technological transition. These dimensions are necessary, but they are not sufficient. Sustainability also depends on how institutions imagine the future, how they make environmental challenges socially meaningful, how they legitimate difficult choices, and how they invite citizens, associations, universities, companies, and local communities to act. This article develops a humanized discourse-analytical account of the role of strategic foresight in overcoming environmental sustainability challenges in Saudi Arabia. It argues that strategic foresight should not be treated simply as prediction, scenario writing, or long-term planning. It is also a communicative practice through which possible futures are narrated, risks are prioritized, responsibilities are distributed, and collective action becomes thinkable. Drawing on critical discourse analysis, the discourse-historical approach, legitimation theory, stakeholder theory, environmental communication, and foresight studies, the article proposes a social framework that connects five pillars: future-oriented environmental awareness, institutional legitimacy and trust, stakeholder voice and participation, actionable environmental communication, and feedback-based learning. The article is conceptual and methodological rather than a report of completed corpus findings. It offers a framework for analyzing public texts produced by Saudi environmental associations and sustainability institutions and for designing clearer, more participatory, and more action-oriented environmental discourse. The contribution is to show that environmental sustainability is not only a technical transition; it is also a discursive and social transition that requires legitimacy, voice, trust, and practical calls to action.